How I solve the problem of writing an formula with just one accolade?

I should write the following formula: This is the code:

$$Q_{sp}=\left\{\stackrel{\frac{\kappa_{0}\kappa_{1}\dots \kappa_{Zp-1}}{\mu_{1}\mu_{2}\dots\mu_{Zp} (1+\sum^{n}_{l=1} \frac{\kappa_{0}\kappa_{1} \dots \kappa_{l-1}}{\mu_{1}\mu_{2}\dots \mu_{l}})} \dots 1\leq Zp\leq number\_pol}{\frac{1}{1+\sum^{n}_{l=1}\frac{\kappa_{0}\kappa_{1} \dots \kappa_{l-1}}{\mu_{1}\mu_{2}\dots \mu_{l}}} \dots Zp=0}$$


How I solve the problem of writing it by just one accolade without having this mistake

!Missing  \right. inserted

• you should add \right. immediately after the last line of the stack. \left always has to be paired with \right, even if one of them is empty. (that's where the period after \right comes in.) Commented Feb 24, 2017 at 19:23
• You should use the dcases environment from mathtools instead. Commented Feb 24, 2017 at 19:27
• How can I use dcases environment? Commented Feb 24, 2017 at 19:30
• @M.amani: I've posted a code. Commented Feb 24, 2017 at 19:53

Example from the manual from AMSmath package page 8.

\documentclass{article}
\usepackage{amsmath}
\begin{document}
\begin{equation*}
\left.
\begin{aligned}
B’&=-\partial\times E,\\
E’&=\partial\times B - 4\pi j,
\end{aligned}
\right\}
\end{equation*}
\end{document}


\documentclass{article}
\usepackage{amsmath}
\begin{document}
$$Q_{sp}=\left\{\stackrel{\frac{\kappa_{0}\kappa_{1}\dots \kappa_{Zp-1}}{\mu_{1}\mu_{2}\dots\mu_{Zp} (1+\sum^{n}_{l=1} \frac{\kappa_{0}\kappa_{1}\dots \kappa_{l-1}}{\mu_{1}\mu_{2}\dots \mu_{l}})} \dots 1\leq Zp\leq number\_pol}{\frac{1}{1+\sum^{n}_{l=1}\frac{\kappa_{0}\kappa_{1} \dots \kappa_{l-1}}{\mu_{1}\mu_{2}\dots \mu_{l}}} \dots Zp=0}\right.$$
\end{document}


Here is a solution with dcases, and some improvements for the vertical spacing:

\documentclass{article}
\usepackage[utf8]{inputenc}
\usepackage{lmodern}
\usepackage{mathtools}

\begin{document}

$$Q_{sp}=\begin{dcases}\stackrel{\frac{\kappa_{0}\kappa_{1} ... \kappa_{Zp-1}}{\mu_{1}\mu_{2} ... \mu_{Zp} \bigl(1+\sum^n_{l=1} \frac{\kappa_{0}\kappa_{1} \dotsm \kappa_{l-1}\mathstrut}{\mu_{1}\mu_{2} ... \mu_{l}}\bigr)} ... 1\leq Zp\leq \text{number\_pol}}{\frac{\strut1}{1+\sum^n_{l=1}\frac{\kappa_{0}\kappa_{1} ... \kappa_{l-1}}{\mu_{1}\mu_{2} ... \mu_{l}}} ... Zp=0} \end{dcases}$$

\end{document}